The immunoregulation of mesenchymal stem cells plays a critical role in improving the prognosis of liver transplantation - Hu, Chenxia; Li, Lanjuan (Journal of translational medicine, 2019)
The liver is supplied by a dual blood supply, including the portal venous system and the hepatic arterial system; thus, the liver organ is exposed to multiple gut microbial products, metabolic products, and toxins; is sensitive to extraneous pathogens; and can develop liver failure, liver cirrhosis and hepatocellular carcinoma (HCC) after short-term or long-term injury. Although liver transplantation (LT) serves as the only effective treatment for patients with end-stage liver diseases, it is not very popular because of the complications and low survival rates. Although the liver is generally termed an immune and tolerogenic organ with adaptive systems consisting of humoral immunity and cell-mediated immunity, a high rejection rate is still the main complication in patients with LT. Growing evidence has shown that mesenchymal stromal cell (MSC) transplantation could serve as an effective immunomodulatory strategy to induce tolerance in various immune-related disorders. MSCs are reported to inhibit the immune response from innate immune cells, including macrophages, dendritic cells (DCs), natural killer cells (NK cells), and natural killer T (NKT) cells, and that from adaptive immune cells, including T cells, B cells and other liver-specific immune cells, for the generation of a tolerogenic microenvironment. In this review, we summarized the relationship between LT and immunoregulation, and we focused on how to improve the effects of MSC transplantation to improve the prognosis of LT. Only after exhaustive clarification of the potential immunoregulatory mechanisms of MSCs in vitro and in vivo can we implement MSC protocols in routine clinical practice to improve LT outcome.